The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1094/pdis-03-15-0350-re
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of Mycosphaerella pinodes to Pyraclostrobin Fungicide

Abstract: Mycosphaerella blight, caused by Mycosphaerella pinodes, is a destructive disease of field pea that is managed using foliar fungicides. Strobilurin fungicides have been used in western Canada for disease management since 2003. To assess the baseline sensitivities of M. pinodes isolates to the strobilurin fungicide pyraclostrobin, the effective concentration to reduce mycelial growth by 50% (EC50) was determined for 70 isolates collected prior to 2003 from Alberta, Saskatchewan, North Dakota, and Washington Sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 34 publications
1
18
0
Order By: Relevance
“…More frequent or heavier use of fungicides in an area may cause a greater shift in sensitivity relative to areas with less frequent use of the same product (Brent and Hollomon 2007). There are many sensitivity studies involving pyraclostrobin and other fungal pathogens in the Pleosporales (Gossen and Anderson 2004;Pasche et al 2004;Mondal et al 2005;Avenot et al 2008;Patel et al 2012;Vega et al 2012;Ahmed et al 2014;Vega and Dewdney 2014;Bowness et al 2016). However, due to natural variation in the fungicide sensitivity of species, different EC 50 values are to be expected (Vega and Dewdney 2014).…”
Section: Discussionmentioning
confidence: 99%
“…More frequent or heavier use of fungicides in an area may cause a greater shift in sensitivity relative to areas with less frequent use of the same product (Brent and Hollomon 2007). There are many sensitivity studies involving pyraclostrobin and other fungal pathogens in the Pleosporales (Gossen and Anderson 2004;Pasche et al 2004;Mondal et al 2005;Avenot et al 2008;Patel et al 2012;Vega et al 2012;Ahmed et al 2014;Vega and Dewdney 2014;Bowness et al 2016). However, due to natural variation in the fungicide sensitivity of species, different EC 50 values are to be expected (Vega and Dewdney 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The colony diameter was determined as the average of two perpendicular measurements after subtracting the diameter of the mycelial plug. The per cent inhibition was calculated relative to the control, and the medium effective concentration (EC 50 ) was calculated using log dose/probit regression line method (Bowness et al., 2016).…”
Section: Methodsmentioning
confidence: 99%
“…Qualitative insensitivity predisposes the pathogen to become completely insensitive to the active ingredient and disease control is no longer achieved at recommended field application rates. Insensitivity to the QoI-fungicides has previously been reported to be qualitative ( Delgado et al, 2013 ; Bowness et al, 2016 ). QoI-resistant D. rabiei isolates have been identified in North Dakota and Montana ( Wise et al, 2008 , 2009 ), where the mechanism of resistance was identified as the G143A mutation in the former ( Delgado et al, 2013 ).…”
Section: Introductionmentioning
confidence: 94%
“…Prior to 2007, it was the only available fungicide MOA on pulse crops and resistance developed rapidly in North Dakota and Canada (Gossen and Anderson, 2004; Wise et al, 2011; Bowness et al, 2016). In 2012, SDHIs were registered for use and these have largely been released as blends with other fungicide MOAs due to the high risk of resistance development.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation